Dysbiosis and Schizophrenia: A Review of Current Evidence on the Gut–Brain Axis and Probiotic Interventions - Anna Jakubiak; grzegorz Karaban; Michał Borawski; Aleksandra Ciuła; Joanna Miśkiewicz; Tadeusz Kuźnieców; Monika Paszkowska; Klaudia Mularczyk; Patrycja Znamirowska; Magdalena Kupis (Quality in Sport)
Introdution: